A constituição da subjetividade do estudante com altas habilidades/superdotação no contexto da sala de recursos multifuncional: contribuições psicanalíticas Freud-Lacanianas - Espanhol, Fernanda Celestino dos Santos (2022)
The main objective of this research was to investigate the scope of Freud-Lacanian psychoanalysis for the construction of the subjectivity of High Abilities or Gifted (HA or G) students who receive Specialized Educational Service (SES), in Multifunctional Resource Rooms (MRR). Psychological knowledge has been asked to walk side by side with the educational field. When it comes to researching about human subjectivity, there it is Psychoanalysis, since its constitution as a science. Hence our interest in psychological theories that permeate the concept and “praxis” of SES of HA or G individuals, and because it is innovative in the research field, since the references found have a certain lack of studies about this theme. We subdivided this dissertation, into the four following chapters. In the first chapter, we tried to answer what are High Abilities or Gifted. And for that we addressed the original concept of gifted, since the beginning of scientific studies. In the second chapter, we made the presentation of the methodology, the course for the bibliographic research, with graphics that match the TDDB research and we entered the constitution of the subjectivity of the HA or G subject identifying psychoanalysis contributions in education with Freud-Lacanian concepts. In the third chapter, we discussed the Public Policies for Inclusive Education of the Gifted Students, during Regular Education in Brazil, the theoretical and hegemonic conceptions in the educational area and how the education of these students takes place. In the fourth and last chapter, we addressed the Contributions of Freud-Lacanian psychoanalysis to the school Inclusion of HA or G students and group activities with HA or G students in the MRR. The research was a literature and documentary review and qualitative approach, in theses ad dissertations, in the scientific databases of the national data of TDDB, in books, magazines and public documents, logbooks, photographs and images about the research theme. We used dialectical historical materialism as a theoretical-methodological framework, in order to identify and analyze contradictions, possibilities and limits of Freud and Lacan’s psychoanalysis for the constitution of the subjectivity of HA or G students. The results indicate that within our investigative proposal of this dissertation, it was possible to find blunt contributions of Freud-Lacanian psychoanalysis in the constitution of the subjectivity of HA or G students in the MRR context. Thus opening hypotheses of studies related to SES and Psychoanalysis, which would bring a greater understanding of the structuring of the subject in the inclusion process. We hope that this research results contribute to a better understanding and care of HA or G students and foster contemporary debates regarding public inclusion policies.